TEENAGERS' PERCEPTIONS OF CITAYAM FASHION WEEK CONTENT ON @ABDULSOFIALLAIL'S TIKTOK ACCOUNT - Ridzki, Annisa Ayu; Darwinsyah, Muhammad (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2024)
Citayam Fashion Week content uploaded on the TikTok @abdulsofiallail feed, researches aim to find out the perceptions of teenagers and what make people interested in the simple fashion information content presented @abdulsofiallail and to find out the perception of teenage from @abdulsofiallail accounts, whether the information presented by TikTok accounts @abdulsofiallail be an up-to-date source and whether TikTok social media can be source of information. In this study, the method used is a qualitative method. Qualitative methods are used to research scientific objects, so the researcher is a key instrument. This study used triangulation acquisition techniques as data collection. This research is descriptive or utilizes qualitative data, this type of research is descriptive qualitative, used to analyze an event or situation socially. This study found 3 main categories based on qualitative coding. First, TikTok as a source of information known to various kinds of news and entertainment can be accessed on these social media. Second, the followers of TikTok accounts @abdulsofiallail cover all circles including teenagers. Thirdly, the disseminator of information is very entertaining with the content it creates. Social media is a medium that has many users and has access to any platform including TikTok and easily gets news and can spread the news, so that teenagers get information and entertainment quickly. As for the reason why the disseminator of information wants to entertain viewers virtually.